De frontière de l’extractivisme à frontière refuge : nouvelles dynamiques régionales autour de la frontière Costa Rica-Nicaragua - Tania Rodríguez Echavarría (Caravelle)
The border between Costa Rica and Nicaragua is a dynamic and porous border region marked by cultural proximity, movements of people and transboundary environmental wealth. However, at the national level, this border has been the subject of numerous conflicts. This article analyzes the most recent political dynamics and tensions in the area. This border is experiencing a new valorization on the one hand with the introduction of pineapple monoculture, a large-scale productive activity that has integrated the frontier into the world market, and with its conversion into refuge territory on the other hand. Border, Agrarian extractivism, Migration, Political refuge, Costa Rica.